MALAYSIA policies and issues IN ECONOMIC DEVELOPMENT (Institute of Strategic and International Studies (ISIS), 2011)
This book provides some answers to these intriguing questions. Chapters in the book trace landmark achievements, and present the challenges and pitfalls faced by the nation over the last five decades after Independence. More important, trhe book is a reminder of the role and contributions of various players and protagonists to the developmental process.